Global, regional, and national time trends in cancer mortality attributable to high fasting plasma glucose: an age-period cohort analysis - Jing Xie; Zeye Liu; Liqun Ren; Liyun He; Shan Lu; Xiangzhi Meng; Xin Zhang; Zhanhao Su; Shenqi Jing; Tao Shan; Junjie Wang; Ruibing Xia; et al. (BMC, 2023)
Abstract Background High fasting plasma glucose (HFPG) is the fastest-growing risk factor for cancer deaths worldwide. We reported the cancer mortality attributable to HFPG at global, regional, and national levels over the past three decades and associations with age, period, and birth cohort. Methods Data for this study were retrieved from the Global Burden of Disease Study 2019, and we used age-period-cohort modelling to estimate age, cohort and period effects, as well as net drift (overall annual percentage change) and local drift (annual percentage change in each age group). Results Over the past 30 years, the global age-standardized mortality rate (ASMR) attributable to HFPG has increased by 27.8%. The ASMR in 2019 was highest in the male population in high sociodemographic index (SDI) areas (8.70; 95% CI, 2.23-18.04). The net drift for mortality was highest in the female population in low SDI areas (2.33; 95% CI, 2.12-2.55). Unfavourable period and cohort effects were found across all SDI quintiles. Cancer subtypes such as "trachea, bronchus, and lung cancers", "colon and rectal cancers", "breast cancer" and "pancreatic cancer" exhibited similar trends. Conclusions The cancer mortality attributable to HFPG has surged during the past three decades. Unfavourable age-period-cohort effects on mortality were observed across all SDI quintiles, and the cancer mortality attributable to HFPG is expected to continue to increase rapidly in the future, particularly in lower SDI locations. This is a grim global public health issue that requires immediate attention.